Implementasi Reward and Punishment dalam Membina Akhlak Siswa di SMP Sinar Husni Medan - Chaniago, Chairunnisa Sahril; Nahar, Syamsu (Jayapangus Press, 2025)
This study aims to describe the implementation of rewards and punishments in fostering student character at SMP Sinar Husni Medan. Character building is an important aspect of Islamic education that prioritizes not only intellectual intelligence but also character formation. The implementation of rewards and punishments is very important as a means of fostering student character by reinforcing positive attitudes and setting limits on negative behavior. Unlike most previous studies that have focused more on aspects of discipline or behavior in general, this study specifically examines character development at the junior high school level. This study uses a descriptive analytical qualitative method with field research. Data collection techniques were conducted through observation, semi-structured interviews, and documentation involving 3 teachers and 5 students. The results of the study indicate that rewards given in verbal and nonverbal forms can motivate students to maintain positive behavior, while punishment is applied gradually and proportionally, including reprimands, minor actions, confiscation of belongings, issuance of warning letters, and summoning of parents, which can limit negative behavior. Most students are able to maintain positive behavior, although a small number still repeat violations. This indicates that character development is not sufficient with rewards and punishments alone but also requires an approach that addresses aspects of awareness and deep understanding of moral values. The reward and punishment method has proven to be a relevant tool for character development and should be applied consistently in shaping a generation of noble character.